ECOLOGICAL STRATEGY OF CONSTRUCTION ENTERPRISE DEVELOPMENT - TKACHENKO, ALLA; BUGRIM, ALEXSANDER (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The development of construction companies requires appropriate environmental strategies. Environmental strategy is a new way to achieve the goals of the business entity. Differences in approaches allow managers to pay attention to the use of appropriate methodological support. This methodological support takes into account the basic requirements that must be involved in the process of strategic planning. This approach ensures the development of a clear strategy to ensure sustainable and long-term competitive advantages of the enterprise. In Ukraine, construction companies are interested in controlling the environmental impact. For the effective implementation of the strategy of the construction company it is important to take into account its environmental component. The contradictory 1nature of the formation of an effective environmental strategy stimulates the optimization of the mechanisms of functioning of international commodity markets. Environmental strategy should be considered in conjunction with the specifics, trends and dynamics of economic decision-making. The best practices of developed countries confirm that sustainable development is impossible without the environmental component. Construction companies are introducing new environmental management standards into production. This is relevant for domestic enterprises to increase their competitiveness. Environmental management is based on a set of forms, methods, tools for managing production processes to achieve environmental and economic efficiency. The purpose of this is to increase the competitiveness of enterprises. Accordingly, the achievement of competitive advantage of the enterprise is based on lower production costs compared to competitors. In addition to this factor, competitiveness is based on an effective management system, active implementation of innovations (including environmentally friendly technologies). The strategy of environmental policy should take into account the real trends of environmental change, the needs of social and economic development of the country on the basis of fundamental doctrinal provisions. For the successful operation of companies, it is important to identify the negative environmental consequences of activities in the construction industry and prevent possible threats in this area.